PENGARUH VOLUME PERDAGANGAN SAHAM DAN RETURN TERHADAP BID-ASK SPREAD SAHAM - R. Hendri Gusaptono (Akutansi Bisnis & Manajemen ( ABM ), 2003)
Inventory holding, order processing and asymmetry are component of cost of bid-ask spread. Two of these costs, inventory holding and The asymmetry information, can not observed be directly, so need a proxi. Trading volume and return can be as inventory holding proxi. This study investigated the influence of trading volume and return to stock bid-ask spread. This case study is taken from telecomunnication industry, that are PT. Telkom and PT. Indosat. The reason choice of these object, because PT. Telkom and PT. Indosat stock are traded actively. The result of this study show that, first independent variable (trading volume and return) and dependent variable (stock bid-ask spread) have significant influence. Second, trading volume to stock bid-ask spread have positive influence. And third return to stock bid-ask spread have negative influence